Interface controlling study of silicon based Schottky diode by organic layer - Imer, Arife Gencer; Korkut, A.; Farooq, W. A.; Dere, A.; Atif, M.; Hanif, Atif; Karabulut, Abdulkerim (Springer, 2019)
The organic layer-on- insulator-semiconductor structures have attracted most attention owing to their great significance on technological applications. The interface of silicon based metal/semiconductor diode was improved using an organic layer. In this study, Sn/p-Si MS contact and Sn/C14H15N3/p-Si MIS heterojunction were fabricated via spin coating method. The electrical parameters of both devices have been investigated, and compared using the current-voltage (I-V) and capacitance-voltage (C-V) data at room temperature. The ideality factor of diodes with and without organic interfacial layer was calculated as 1.33 and 1.28, respectively. The values of barrier height were estimated as 0.69 and 0.81 eV for the MS and MIS type structure, respectively. Additionally, the values of series resistances for both diodes were determined as 1.27 and 1.19 k omega from Norde functions, respectively. The barrier height values were also examined using the reverse bias C-2-V characteristics for both diodes, and compared with results obtained from I to V data. The experimental results confirmed that the barrier height of Sn/C14H15N3/p-Si MIS structure is considerably higher than that of traditional Sn/p-Si MS diode. The performance and quality of these type devices could be improved and controlled by inserting the organic interfacial layer between the metal and semiconductor.
Keywords: Barrier Height Enhancement; N-Type Silicon/Metal; I-V-T; Electrical Characteristics; Photovoltaic Properties; Junction; Semiconductors; Temperature; Performance; Mechanism